Ethno-mathematic Design in Statistical Analysis Content (Numeracy Literacy Development Study) - Wandra Irvandi; Yudi Darma (Riemann: Research of Mathematics and Mathematics Education, 2024)
The mathematics learning process can be carried out by using and utilizing social phenomena, culture, and other aspects. In the past and currently, mathematics has developed in culture and society, even integrating culture with mathematics. Therefore, it is necessary to involve existing phenomena to overcome various existing problems, including mathematical problems. Therefore, it is necessary to teach mathematics in schools by depicting the context of the origin of mathematical ideas by utilizing culture so that it becomes meaningful learning for students, in this case called ethnomathematics. This short article tries to examine Ethnomathematics Design. In Statistical Analysis Content (Numeracy Literacy Development Study). The method used in this research is ethnography with a qualitative approach. The research results show that the development of ethnomathematics design can go through the definition stage to the initial development stage. From this development stage, an ethnomathematics design in statistical analysis content was produced. The design of ethnomathematics in statistical analysis content is a must-see for the philosophical value of ethnomathematics in its development.